ABSAC: Attribute-Based Access Control Model Supporting Anonymous Access for Smart Cities - Zhang, Runnan; Liu, Gang; Li, Shancang; Wei, Yongheng; Wang, Quan (Security and communication networks, 2021)
Smart cities require new access control models for Internet of Things (IoT) devices that preserve user privacy while guaranteeing scalability and efficiency. Researchers believe that anonymous access can protect the private information even if the private information is not stored in authorization organization. Many attribute-based access control (ABAC) models that support anonymous access expose the attributes of the subject to the authorization organization during the authorization process, which allows the authorization organization to obtain the attributes of the subject and infer the identity of the subject. The ABAC with anonymous access proposed in this paper called ABSAC strengthens the identity-less of ABAC by combining homomorphic attribute-based signatures (HABSs) which does not send the subject attributes to the authorization organization, reducing the risk of subject identity re-identification. It is a secure anonymous access framework. Tests show that the performance of ABSAC implementation is similar to ABAC’s performance.